Global burden of cardiovascular diseases attributable to hypertension in young adults from 1990 to 2019. Issue 12 (December 2021) - Liu, Jing; Bu, Xiang; Wei, Linyan; Wang, Xiqiang; Lai, Lulu; Dong, Caijuan; Ma, Aiqun; Wang, Tingzhong
Abstract : Background: Hypertension grows into a serious public health problem among young adults, linking to a set of life-threatening cardiovascular diseases (CVDs). Young adults are not well represented in current knowledge about the CVDs burden attributable to hypertension. Methods: In this analysis of data from the GBD (Global Burden of Disease) study 2019, we focus on young adults and provide the first comprehensive and comparative assessment of the hypertension attributable CVDs burden, in terms of its mortality and years of living with disability (YLD) from 1990 to 2019, stratified by location, sex, and development status. Results: Globally in 2019, the death and YLD numbers caused by hypertension-related CVDs were 640 239 and 2 717 474 in young adults, marking a 43.0 and 86.6% increase from 1990, respectively. The corresponding mortality rate dropped by 10.5%, whereas the YLD rate increased by 16.8% during the same period. V-shaped association between CVDs burden and social development status was observed. The largest burden and the most pronounced increase were borne by middle-income countries, while high-income countries had the lowest death/YLD rate with a quicker annual decline. Men largely outpaced women in hypertension attributable CVDs mortality. Ischemic heart disease and stroke were the leading cause for death and YLD burden, correspondingly. Conclusions: Hypertension attributable CVDs burden in young adults has greatly increased from 1990 to 2019, with considerably spatiotemporal and sexual heterogeneity. The largest burden was borne by middle-income countries, especially by men. Establishment of geographically and sexually tailored strategies were needed to prevent hypertension-related CVDs in young adults. Abstract : Supplemental Digital Content is available in the text